Modelling Of The Property Market: The Malaysian Experience - Kamarudin, Norhaya; Ismail, Suriatini; Mohd. Ali, Hishamuddin; Sipan, Ibrahim @ Atan; Mahamud, Rosadah (2008)
Property market modelling is an attempt to understand behaviours of the property market where models present theoretical underpinning of the property market, which forms the micro foundation of property market behaviour. The abundant literature on it suggests the popular nature of the approach in understanding property market problems. Despite the problems encountered in modelling the property market, many more attempts being made to achieve more accurate models. The Malaysian experience in this field is relatively new but nevertheless it has significant contribution towards the development in the real estate research.